CREATIVE ECONOMIC DEVELOPMENT STRATEGY FOR THE CRAFT SUB-SECTOR - Jailani, Novalini; Adinugraha, Hendri Hermawan; Ismanto, Kuat (Manis: Jurnal Manajemen dan Bisnis, 2023)
This study aims to formulate alternative strategies for developing the creative economy in the craft subsector. This research was conducted by field research with a descriptive qualitative approach. Data collection is done by conducting interviews, observation and documentation. Primary data sources were obtained from direct interviews with owner and production manager of Ridaka Woven & Craft. Secondary data were obtained from various books, articles, journals and authoritative websites relevant to this research. Data were analyzed using the SWOT analysis technique by identifying internal factors which are strengths and weaknesses, as well as external factors which are opportunities and threats for business development. The results of this study found that to be able to develop its business, Ridaka Woven & Craft can apply several strategies, namely: 1) with sufficient raw materials it can continue to innovate products in terms of motifs and types that suit market tastes in order to make handicraft products competitive. Then always maintaining the characteristics of ecofriendly products to reach the global market which is currently a trend of using products that are environmentally friendly. 2) Maximizing the role of social media and the internet as promotional and marketing media. 3) Conduct skills training and knowledge development to improve the quality of human resources. 4) Frequently participating in events and bazaars can also be an effort to promote products and brands. 5) The government always supports by providing information to build people's mindset about handicraft products as local brands.